2005
DOI: 10.1300/j047v17n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Model of Perceived Food Quality Determinants

Abstract: This research tries to understand the consumer's perception of quality of food and analyze different contributions concerning it. The Testing Model has been designed based on the main dimensions of perceived quality of food, results will emphasize the sensitive perception that permits to assess this quality by the consumer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 46 publications
1
8
0
2
Order By: Relevance
“…Structural equation modeling ( SEM ) is used to describe the correlational structure among observed and latent variables. In the framework of sensory analysis, several studies have demonstrated the suitability of SEM for testing theoretical prepositions referring to how latent variables are linked to empirical data and the direction of that relationship (Abdi, Valentin, Chollet, & Chrea, ; Alonso, Gallego, & Mangin, ; Martínez‐Carrasco, Brugarolas, Martínez‐Poveda, Ruiz, & García‐Martínez, ; Vilela, Marques, & Correia, ). According to Hair et al (), the SEM approach comprises two types of models: measurement and structural.…”
Section: Discussionmentioning
confidence: 99%
“…Structural equation modeling ( SEM ) is used to describe the correlational structure among observed and latent variables. In the framework of sensory analysis, several studies have demonstrated the suitability of SEM for testing theoretical prepositions referring to how latent variables are linked to empirical data and the direction of that relationship (Abdi, Valentin, Chollet, & Chrea, ; Alonso, Gallego, & Mangin, ; Martínez‐Carrasco, Brugarolas, Martínez‐Poveda, Ruiz, & García‐Martínez, ; Vilela, Marques, & Correia, ). According to Hair et al (), the SEM approach comprises two types of models: measurement and structural.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely acknowledged that food quality (Sulek and Hensley, 2004; Othman et al , 2012; Kong and Mohd Jamil, 2014), service elements (Pratten, 2003; Chu et al , 2005; Edwards and Meiselman, 2005), staff competency (Clemes et al , 2013; Adam et al , 2014; Döring and Wansink, 2016) and certification (Alonso et al , 2005; Kim et al , 2006; Ha and Jang, 2010; Haghighi et al , 2012) are common attributes that significantly influence customers’ decision to eat, satisfaction and repurchasing intention in the commercial foodservice setting. Based on Caruana et al (2000) and Ryu and Han (2010), perceived value would often play a moderating role between foodservice attributes against satisfaction and customer repurchase intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, qualitative losses which subjective and abstract phenomenon is difficult directly [35] and rather described in terms of or state of the product in question [8, complicated, obtained in each PHLs can be estimated to total production [45]. Alternatively, a model could be obtained cumulative weight losses respect to the total which is more of a difficult to measure of perceived value [8,9,50]. Though not be ignored; complete picture without measurement of qualitative generalized but instead valued factors for each by [50] quality of determined based on perception of quality.…”
Section: Figure 2 Description Of Postharvestmentioning
confidence: 99%
“…Discarded volume can be likened to quantitative which is measurable by the cumulative discarded weight as produce moves along the Furthermore, as fresh produce move down their perceived quality which is a function intrinsic attributes [8,9] such as fruit color, freedom from defects [8,9,16,26] also change to the postharvest handling and market Perceived quality could therefore be used estimate qualitative losses in plantain; making losses becomes a latent variable in this case A mathematical way to view this is quantitative applies when perceived quality reaches zero is unusable and therefore discarded. At this Journal of Business and Economics Research 2014; 3(6-1): 31system gives a general supply chain and can holistic assessment of production and is the logical first losses and appropriate to de-categorize all (postharvest handling and into their tiniest bits contribution to the overall framework for such supply chain.…”
Section: Frameworkmentioning
confidence: 99%